ChemInform Abstract: A Cu‐Catalyzed Four‐Component Cascade Reaction to Construct β‐Ester‐γ‐amino Ketones. Issue 42 (September 2016) - Ling, Jiayue; Zhang, Jie; Zhao, Yanwei; Xu, Yudong; Wang, Hanghang; Lv, Yuanzheng; Ji, Meishan; Ma, Liang; Ma, Meihua; Wan, Xiaobing
Abstract: The title ketones are prepared from readily available styrenes, diazo compounds, and amines.